Lupus Never Fails to Deceive US: A Case of Rowell's Syndrome. (23rd September 2020) - Arevalo, Ana B.; Nassar, Rawann; Krishan, Satyam; Lakshmanan, Priyanka; Salgado, Maria; Chokshi, Priya
Abstract : Background . Rowell's syndrome is comprised of the presentation of erythema multiforme- (EM-) like lesions in association with lupus erythematosus (LE), along with serologies of speckled antinuclear antibodies (ANAs), positive rheumatoid factor (RF), positive anti-La/anti-Ro, and the clinical finding of chilblains. As per the redefined criteria by Zeitouni et al., three major criteria in addition to at least 1 minor criterion are necessary for diagnosis. Case Presentation . A 20-year-old male presented with a one-week history of worsening nonpruritic erythematous maculopapular skin rash (resembling EM) which appeared on the face and subsequently spread to the trunk, arms, legs, palms, and soles. There was no mucosal involvement. At the onset of rash, the patient reported headaches, associated with photosensitivity and intermittent fevers. Workup for viral meningitis yielded negative results. Laboratory investigation revealed mild anemia, elevated inflammatory markers, a positive ANA with speckled pattern, a positive anti-Ro/SSA, anti-La/SSB antibodies, and a positive rheumatoid factor (RF). Lupus anticoagulant antibody was positive along with a low-positive anticardiolipin IgM antibody and a negative beta-2 glycoprotein antibody. Anti-dsDNA, anti-Smith, anti-Jo-1, anti-centromere, and anti-Scl-70 antibodies were negative. Hepatitis serologies, herpes simplex virus 1 and 2, mycoplasma, Epstein–Barr virus, HIV, and parvovirus B19 were negative. Left arm skin biopsy demonstrated vacuolar interface dermatitis and positive colloidal iron stain suggestive of dermal mucin deposition, favoring the diagnosis of cutaneous collagen vascular disease. Cutaneous lesions improved with administration of oral prednisolone. Conclusion . Rowell's syndrome should be considered in patients who present with cutaneous LE and lesions resembling EM. Further serological markers should be pursued in the absence of obvious EM-precipitating factors.